Improving the capacity and diversity of local public health workforce to address climate impacts to health through community partnerships and problem-based learning - Schmeltz, Michael T.; Ganesh, Chandrakala (Frontiers in Public Health, 2023)
Almost all aspects of society are affected by our changing climate. Individuals and communities experience the health impacts associated with climate change most often in their everyday lives. Undergraduate students in public health programs are no different and increasing both the knowledge and capacity to respond to the health impacts of climate change will be imperative for future public health leaders. This manuscript will highlight three case studies in how problem-based learning was used by California State University, East Bay’s Department of Public Health undergraduate students to address climate change issues for local community and government organizations. The results from problem-based learning collaborations between undergraduate students and community and government organizations have been mutually beneficial and increased the knowledge and workforce capacity of climate and health in the San Francisco Bay Area. The authors believe the use of problem-based learning is an effective model to achieve these goals. Both the students and the community benefit from these experiences and results of projects that enhance an organization's ability to prepare for and respond to climate change in their communities.